Fractionation of the constituents of lemon oil by gas-partition chromatography - Manotok, Teresa T.
The components of the oil of the ?kabuyao?, a local variety of lemon, were determined by running the oil through a gas chromatograph. The components of the sample were separated according to their respective affinities for the material with which the column is filled, the component having the least affinity for the column material passing through first. These components were registered on a stripchart as peaks.